POLICY ON CONTROL OF PLAGUE EPIDEMIC IN SEMIRECHENSK REGION (1900-1910 S) (Scientific journal of the Fergana State University, 2024)
In this article, veterinary policy, infectious diseases spread among livestock (especially plague), activities of veterinary doctors and veterinary paramedics in Semirechensk region at the beginning of the 20th century are highlighted. Veterinary service was established earlier in Semirechensk region than in Syrdarya, Fergana, Samarkand, Transcaspian regions. In this region, the fight against cattle plague began in 1897, in the first two years, data on epizootics were collected, and in 1899, the fight against plague was carried out in the region. However, people began to say that the veterinary measures carried out in the society are useless and cause financial damage to the population. Non-specialists complained that veterinarians were using their efforts to combat plague epizootics by killing infected livestock, and proposed a treatment and prevention measure that included treating animals with copper powder. It was also suggested that healthy animals lick dead animals and even put diseased animals to the wind. Experts suggest a method of vaccinating domestic animals, which are brought to pastures to graze, taking into account the fact that wild animals in Semirechensk mountains are infected with plague from animals that are resistant to plague to domestic animals in the pastures during the summer. We will discuss these issues in more detail in the article.